Challenges and opportunities associated with development of small and medium enterprises in jaffna district - Sathana, V.; Velnampy, T.; Rajumesh, S. (University of Jaffna, 2016)
With the globalization trend, Small and Medium Enterprises (SMEs) are in rapidly growing and developing arena. It has momentous influences on the prolific changes in all countries, and they are major contributor for inclusive economic growth, regional development, employment generation and poverty reduction in Sri Lanka. This research was conducted to diagnose the awesome challenges and opportunities of SMEs in the existing situation of Jaffna District. Further this paper reviewed the existing literature, empirical studies as well as the prevailing data bases in order to identify the challenges and opportunities for the development of SMEs in the Jaffna District. Researcher conducted qualitative exploratory research; explain the phenomenon of problematic situation of SMEs in Jaffna District. Purposive sampling technique was the sampling method, primary data collection method was used to collect the data, and structured interview was conducted with the 37 heads of community development institution in the Jaffna district. This study revealed that end of the war crafted peace environment in Sri Lanka, Many problems and challenges are faced by SMEs in Jaffna District in this post war situation, SMEs in Jaffna District are in the embryonic stage comparing with SMEs in other district in Sri Lanka and there are vast opportunities and unutilized resources for industrial expansions in this SME sector in Jaffna District. This industrial enlargement will create more market opportunities to the SMEs. The important implication of this study is that the SME sector is envisaged opportunities to contribute to transform lagging regions into emerging regions of prosperity.
Keywords: Challenges and opportunities; Development; Small and Medium Enterprises (SMEs)